Optimizing Enterprise Resource Planning (ERP) Systems for Agile Decision-Making in the Digital Transformation Era - Kustiyono, Kustiyono; Amiro, Suratno; Rahayuningsih, Lisa (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
In the era of digital transformation, businesses are increasingly relying on Enterprise Resource Planning (ERP) systems to enhance operational efficiency and decision-making agility. This research explores how ERP systems can be optimized to support agile decision-making processes, which are essential for organizations to remain competitive and adaptive to rapid technological changes. With the growing complexity and volume of data, traditional ERP systems may not fully meet the dynamic requirements of modern businesses, thus necessitating enhancements that enable faster, data-driven decision-making. The study employs a qualitative approach, gathering insights from ERP users and experts across various industries. The research investigates the challenges faced by organizations in utilizing ERP systems for agile decision-making, focusing on system integration, real-time data processing, and user adaptability. Furthermore, it identifies the critical features that ERP systems must have to enhance decision-making flexibility, including advanced analytics capabilities, cloud-based functionalities, and seamless integration with emerging technologies like Artificial Intelligence (AI) and the Internet of Things (IoT). The findings suggest that ERP systems need to evolve beyond traditional transactional functionalities, incorporating agile methodologies that prioritize rapid information processing and real-time responsiveness. Additionally, the study highlights the importance of organizational culture and training in maximizing the benefits of these optimized ERP systems. This research contributes to the understanding of how ERP systems can be leveraged as a strategic tool for agile decision-making in the digital transformation era. The study provides actionable insights for both practitioners and scholars, offering a framework for enhancing ERP system capabilities to meet the evolving demands of modern businesses. Recommendations for future research include the exploration of specific ERP tools and strategies that can further improve decision-making agility in various sectors.